Fever of unknown origin. A changing clinical spectrum and a diagnostic challenge - Moisés Casarrubias-Ramírez (Case Reports)
This issue of Case Reports presents two cases of fever of unknown origin (FUO) that illustrate the etiological diversity and diagnostic complexity of this condition.